Doing more digital humanities : open approaches to creation, growth, and development - Crompton, Constance (Constance Louise Kathleen); Lane, Richard J., 1966-; Siemens, Raymond George, 1966- (London ; New York, NY : Routledge/Taylor & Francis Group, 2020)
"As digital media, tools, and techniques continue to impact and advance the humanities, Doing More Digital Humanities provides practical information on how to do digital humanities work. This book offers: A comprehensive, practical guide to the digital humanities ; Accessible introductions, which in turn provide the grounding for the more advanced chapters within the book ; An overview of core competencies, to help research teams, administrators, and allied groups, make informed decisions about suitable collaborators, skills development, and workflow ; Guidance for individuals, collaborative teams, and academic managers who support digital humanities researchers ; Contextualized case studies, including examples of projects, tools, centres, labs, and research clusters ; Resources for starting digital humanities projects, including links to further readings, training materials and exercises, and resources beyond ; Additional augmented content that complements the guidance and case studies in Doing Digital Humanities"--
Legacy technologies and digital futures / Laura Estill -- Getting started : strategies for DH professional development / Paige Morgan -- Negotiating sustainability : building digital humanities projects that last / Lisa Goddard and Dan Seeman -- DH and humanities workflows : two case studies / Scott Paul McGinnis -- Text processing techniques & traditions (or: why the history of computing matters to DH) / John W. Maxwell -- Origins, images and stereotypes : digital humanities and its organisational context / Claire Warwick -- What is Linux and what's it doing in the digital humanities? / Jon Martin -- Beyond "whiz-bang" : 3D printing and critical making in the humanities / Aaron Tucker -- 3D visualization for the humanities / Alex Razoumov -- Where data meets design : a vision for visualization in the digital humanities / Aimée Knight -- Doing digital humanities with digital storytelling / John Barber -- "Bodying" digital humanities : considering bodies in practice / Jessica Rajko -- Ontologies for digital humanists / Christine Walde, Jana Millar-Usiskin, and Caroline Winter -- Big data analytics for multiscale seading / Belaid Moa and Stephen Ross -- Starting with students : open course design / Christopher Friend, Robin DeRosa, and Jesse Stommel -- The undergraduate summer intensive : principles of pedagogy and design / Emily Murphy, Shannon Smith and Brian Greenspan -- Building DH training events / James Cummings -- New fundaments for a multi-modal space-time : teaching 3D : what it is, and why it matters / John Bonnett -- Opportunities for social knowledge creation in the digital humanities / Alyssa Arbuckle -- Models for DH at liberal arts colleges and four year institutions / Janet Simons and Angel Nieves.
Includes bibliographical references and index.
Print version record.
Constance Crompton is Canada Research Chair in Digital Humanities and Assistant Professor in the Department of Communication at the University of Ottawa. Richard J. Lane is Professor of English at Vancouver Island University and Principle Investigator for the MeTA Digital Humanities Lab. Ray Siemens is Distinguished Professor in the Faculty of Humanities at the University of Victoria, in English and Computer Science.
eBooks on EBSCOhost
Keywords: Digital humanities; Humanities -- Research -- Methodology; Humanities -- Study and teaching (Higher); Internet in education; Sciences humaines numériques.; Internet en éducation.; digital humanities; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science; Digital humanities; Humanities -- Research -- Methodology; Humanities -- Study and teaching (Higher); Internet in education